2019
DOI: 10.1021/jacs.8b13882
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Nanoshell-Functionalized Polymer Nanoswimmer for Photomechanical Poration of Single-Cell Membrane

Abstract: We report an ultrasound-driven gold-nanoshell-functionalized polymer multilayer tubular nanoswimmer that can photomechanically perforate the membrane of a cancer cell by assistance of near-infrared (NIR) light. The nanoswimmers were constructed by a template-assisted layer-by-layer technique and subsequent functionalization of Au nanoshells inside the big opening. The nanoswimmers exhibit efficient and controllable movement toward target cells through the manipulation of the acoustic field. Next, the nanoswimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
144
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(147 citation statements)
references
References 54 publications
1
144
0
2
Order By: Relevance
“…Apart from the autonomous motion, the movement of swimming nanorobots can be operated toward specific cell in vitro conveniently by regulating the externally physical signal, including light gradient, acoustic frequency, and magnetic direction 39,40,50 . As shown in Figure 2C, swimming nanorobots could be autonomously navigated to target the cell membrane.…”
Section: Basics Of Swimming Nanorobot and Cell Membranementioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the autonomous motion, the movement of swimming nanorobots can be operated toward specific cell in vitro conveniently by regulating the externally physical signal, including light gradient, acoustic frequency, and magnetic direction 39,40,50 . As shown in Figure 2C, swimming nanorobots could be autonomously navigated to target the cell membrane.…”
Section: Basics Of Swimming Nanorobot and Cell Membranementioning
confidence: 99%
“…Considered the drive force is not enough to open the cell membrane, recent efforts attempt to realize the swimming nanorobot to perforate cell membrane through addition of extra forces. The swimming nanorobot achieved mechanical opening of cell membrane with the assistance of NIR light irradiation 40 . The gold nanoshell‐functionalized polymer tubular swimming nanorobot with a length of 10 μm possesses asymmetric geometry along the long axis (big opening of ∼800 nm, and small opening of ∼200 nm).…”
Section: Mechanically Opening a Cell Membranementioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, synthetic and biological membranes have found their applications in the field water purification [18], dialysis [19] and targeted gene and drug delivery [20]. Especially in biomedical researches, the interaction of motile particles with biological membranes should be fully understood to explain the delivery of cargo to the interior of the cells [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, synthetic membranes are now routinely used already for applications from water purification [5,6] to dialysis [7,8] and can be regarded as a paradigmatic success of biomimetics [9][10][11]. Future perspectives for the usage of synthetic membranes involve problems like targeted gene and drug delivery to (cancer) cells [12][13][14][15][16][17][18][19][20][21][22][23][24] or, more generally, the delivery of cargo to the interior of synthetic droplets, requiring a precise understanding of the interaction of motile particles with synthetic and biological membranes. Evidence from previous studies has shown that the physical uptake by living cells is strongly affected by the particle and membrane physicochemical and functional properties [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%